New records of two rare neuropterans (Insecta: Neuroptera) in Slovenia - Petra Devetak (Natura Sloveniae)
Two neuropteran species, the antlion Neuroleon microstenus (McLachlan 1898) and the mantispid Mantispa aphavexelte Aspöck & Aspöck 1994, are known as extremely rare in Slovenia. New records of the species are presented. Both neuropterans occur only in the Submediterranean region of the country. Due to the insufficient knowledge of its ecology, the threat status of M. aphavexelte is unknown, whilst N. microstenus should be considered as endangered considering that its habitats are shrinking